Proposal of International Council for Harmonization (ICH) Guideline for the Approval of Biosimilars. Issue 1 (1st January 2023) - Niazi, Sarfaraz K.; Al-Shaqha, Waleed Mohammed; Mirza, Zafar
ABSTRACT: Objectives: Since the initial release of biosimilars 18 years ago, regulations for their licensing have changed considerably; however, there is no global consensus on these regulations. Establishing harmonized regulatory guidelines for the approval of biosimilars with support from the ICH, an independent, non-profit association under Swiss law, will significantly enhance the affordability of biological drugs. Methods: Regulatory guidelines from the Food and Drug Administration (FDA), European Medicines Agency (EMA), Medicines and Healthcare products Regulatory Agency (MHRA), and World Health Organization (WHO) were analyzed for historical changes and elements critical to the safety and efficacy of biosimilars. Results: Analysis of all EMA and FDA filings show that none of the animal testing and clinical efficacy testing failed because animals do not have the required receptors to initiate pharmacologic responses, and efficacy studies cannot be statistically powered to conclude any results. New analytical technologies will enable good biosimilarity determination, avoiding both tests. Conclusion: Scientifically based ICH guidelines that remove redundant studies will reduce development costs, improve safety, and allow global drug distribution based on single compliance. These guidelines are particularly necessary for emerging countries lacking the expertise and resources to evaluate biosimilar filings.